Municipal Citizen Service Centers in Southeastern Europe : Survey Results on Success Factors, Challenges, and the Human Rights Approach of Municipal One-Stop Shops in the Western Balkans - Pfeil, Helene; Agarwal, Sanjay; Schott, Berenike (World Bank, Washington, DC, 2017)
This report presents the results of an online survey administered in six southeastern European countries: Albania, Bosnia and Herzegovina, Kosovo, Macedonia, Montenegro and Serbia. The survey was aimed at gathering insights related to the operations and human rights approach of municipalone-stop shops delivering services to citizens. Findings show that the region’s municipal citizen service centers are generally aware of the impact that their activities have on human rights. In addition to complying with legal requirements to guarantee the rights of citizens and avoid discriminatory practices in service delivery, many citizen service centers actively promote universal access to public services. This is mostly accomplished by taking measures that foster theinclusion of vulnerable groups and by offering mechanisms that encourage participation and accountability, such as citizen feedback and complaint-handling mechanisms.